Utah's UTOPIA an ethernet-based MPLS and VPLS triple play deployment. - Moerman, Ken.
Broadband in North America is now at critical mass, passing the inflection point from the early adopter to the early majority. In fact, Strategy Analytics predicts that by 2010, over 78 million U.S. households will have some form of broadband connectivity, much of it capable of delivering the triple play of voice, video, and high-speed Internet access. Their providers will consist of local exchange carriers, multiservice operators, and municipalities that have deployed their own triple play networks. Why the municipalities, and what do they bring to the table? In many instances, smaller cities and towns have been bypassed by the first phases of the incumbent operators' triple play deployments. For reasons of economic development, quality of living, education, and the retention of skilled workforces, the government has stepped in to fill the void. This article looks at the most ambitious municipality-driven triple play deployment in North America, the UTOPIA MetroNet in Utah. The system integrator for UTOPIA is DynamicCity, which early on defined a set of design principles that would make the network successful. These included the requirement that the network be open to multiple service providers, be carrier class, be scalable and based on future-proof technology, and that the architecture be based on open standards while keeping costs to a minimum. The article first reviews some of the considerations behind the choice of the technology and deployment approach based on these guidelines, and then describes in detail the network topology and services architecture, the current status of the deployment, and future plans. Specific topics covered include the use of multiprotocol label switching/virtual private LAN service, IP multicasting, and traffic engineering.
Keywords: Ethernet-based MPLS; IP multicasting; QoS; UTOPIA MetroNet; VPLS; multiple service providers; multiprotocol label switching; municipality triple play deployment; network topology; quality of service; services architecture; traffic engineering; virtual private LAN service